2010
DOI: 10.1016/j.eurpolymj.2009.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Internal structure and linear viscoelastic properties of EVA/asphalt nanocomposites

Abstract: The effect of the addition of two different organoclays as a third component in polymer modified asphalts has been investigated. Ternary mixtures were prepared by adding clay and poly(ethylene-covinylacetate) to the asphalt, either separately, or in the form of a premixed master batch. The performed characterizations allowed the determination of how the two methods of mixing influence the interactions between asphalt and polymer and therefore the final rheological properties. In particular, it was shown that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(41 citation statements)
references
References 53 publications
(41 reference statements)
2
38
0
1
Order By: Relevance
“…Of course, the polymer being the one that is more difficult to move among the clay interlayers, the MB procedure had a favorable starting condition, in which half of the procedure is already completed and only the "ease to move" asphalt molecules remain to intercalate the clay. A second analogous study was performed by using EVA as a polymeric modifier and by comparing the effect of two different organoclays [316,317]: 20A and Dellite 43B (subsequently referred to as 43B), an OMMT modified using dimethyl dibenzyl hydrogenated tallow-ammonium. The results paralleled those just described for SBS: the binary blend was markedly biphasic, the two clays worked as compatibilizers, and the MB procedure gave better results than the PM procedure in both cases.…”
Section: The Asphalt-polymer-clay Ternary Systemmentioning
confidence: 99%
“…Of course, the polymer being the one that is more difficult to move among the clay interlayers, the MB procedure had a favorable starting condition, in which half of the procedure is already completed and only the "ease to move" asphalt molecules remain to intercalate the clay. A second analogous study was performed by using EVA as a polymeric modifier and by comparing the effect of two different organoclays [316,317]: 20A and Dellite 43B (subsequently referred to as 43B), an OMMT modified using dimethyl dibenzyl hydrogenated tallow-ammonium. The results paralleled those just described for SBS: the binary blend was markedly biphasic, the two clays worked as compatibilizers, and the MB procedure gave better results than the PM procedure in both cases.…”
Section: The Asphalt-polymer-clay Ternary Systemmentioning
confidence: 99%
“…Ternary blends of polymer, bitumen and nanoclay can be prepared using conventional polymer processing techniques. Sureshkumar and co-workers showed that nanoclay can act as a compatibiliser for EVA-bitumen blends and influence the rheological behaviour of these systems (Sureshkumar et al, 2010). Similarly, Galooyak et al reported a further improvement in storage stability when a nanoclay was added to a SBS-bitumen blend (Galooyak et al, 2010).…”
Section: © Woodhead Publishing Limited 2011mentioning
confidence: 96%
“…Besides the application of PMCs with nanoclays in buildings, its use in asphalt and bitumen production is widely referred as beneficial to their physical and mechanical properties [17], [36], [37]. For all the presented reasons, clay-based nanocomposites are the nanoparticles most examined and tested for the construction industry.…”
Section: Nanoclaymentioning
confidence: 98%